Using innovative technologies (Coursera platform) in the formation of intercultural competence - Baisov, Axmad (The Lingua Spectrum, 2024)
The integration of innovative technologies and educational materials is a key focus in developing intercultural competence within modern education systems. Tools like online learning platforms (e.g., Coursera, EdX), VR/AR technologies, and multimedia resources play a vital role in enhancing global cultural awareness among students. Platforms like Coursera, offering flexible, international-standard courses, align with the goals of Uzbekistan’s educational reforms, particularly since the 2020 emphasis on innovative pedagogy and online education. Despite their potential, challenges such as language barriers, credit system incompatibilities, and cost constraints limit Coursera’s suitability for Uzbek students. Many courses are offered only in English, and their recognition within the national system remains unresolved. Adapting these courses to local contexts, improving affordability, and fostering collaborations with national universities could address these issues. With such adjustments, Coursera could significantly elevate the quality of education and global competitiveness of Uzbekistan’s higher education sector.